Микрофитобентос залива Тартус (Сирия, Средиземное море) - Герасимюк, В.П. (Альгология, 2017)
Представлены данные о микроскопических водорослях залива Тартус. В результате обработки 38 проб было определено 63 вида водорослей, которые относятся к 2 отделам. Диатомовые (59 видов) водоросли преобладали по видовому составу над синезелеными (4). Доминирующими видами Bacillariophyta в заливе были Melosira moniliformis (O. Müll.) C. Agardh, Odontella aurita (Lyngb.) C. Agardh, Tabularia tabulata (Agardh) Snoeijs, Licmophora abbreviata C. Agardh, Achnanthes brevipes C. Agardh. In the microphytobenthos of the Gulf of Tartus (Syrian coast of the Mediterranean Sea) 63 species of microscopic algae were revealed. They belong to 35 genera, 24 families, 17 orders, 5 classes, and 2 divisions. Bacillariophyta (59 species) lead in species number; cyanobacteria were represented by 4 species. In their ecological features, most algae are alkaliphilic and mesosaprobic. In terms of biogeography, algae of the Gulf of Tartus represent cosmopolitan and boreal groups with arctic-boreal and tropical elements. Dominating species of Bacillariophyta in the microphytobenthos of the Gulf of Tartus were Melosira moniliformis (O. Müll.) C. Agardh, Odontella aurita (Lyngb.) C. Agardh, Tabularia tabulata (Agardh) Snoeijs, Licmophora abbreviata C. Agardh, and Achnanthes brevipes C. Agardh.